An Overview of Smart Aquaculture: IoT-Based Domestication Strategies for the Channa Genus - Rizal Akbar Hutagalung; Muhammad Fitri Yusof; Celestino da Cunha Barreto (Journal of Aquaculture Science, 2026)
Aquaculture continues to expand as a key contributor to global food security, yet the domestication of biologically sensitive and behaviorally aggressive species remains a major constraint in production systems. The genus Channa (snakehead fish) represents a high-value freshwater taxon whose culture development is limited by physiological sensitivity to environmental fluctuations, pronounced intra-specific aggression, and feeding instability under captive conditions. This overview summarizes the latest literature on the application of Internet of Things (IoT) technology in aquaculture and explores the consistency of this trend in other species, which may be relevant to the challenges of domestication in Channa. Previous studies on IoT use show that IoT-based systems are primarily used for real-time water quality monitoring and precision feeding management. Continuous monitoring of water quality using IoT provides better environmental stability, earlier detection of deviations, and reduced losses from stress compared to conventional manual observation. Simultaneously, automated and sensor-supported feeding strategies demonstrate improved feed conversion efficiency, reduced feed waste, and better regulation of feeding frequency. The literature as a whole shows that aquaculture is evolving towards more modern, controlled, technology- and data-based systems that are more efficient in resource use. Although empirical validation in Channa culture systems remains limited, further controlled experimental studies are required to assess the applicability of IoT-based management strategies in this genus.